2003
DOI: 10.1364/ol.28.001933
|View full text |Cite
|
Sign up to set email alerts
|

Ho:YAG laser intracavity pumped by a diode-pumped Tm:YLF laser

Abstract: We report a compact Ho:YAG laser that is intracavity pumped by a diode-pumped Tm:YLF laser. Both lasers exhibit pulse mode behavior. Operating both crystals at room temperature (25 degrees C), we obtained 1.6 W of average output at 2.09 microm from the Ho:YAG laser for 15.4 W of diode power incident upon the Tm:YLF rod and a slope efficiency of 21%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 8 publications
1
50
0
Order By: Relevance
“…Such a strong absorption, even when partially saturated, should dominate any other losses in the thulium cavity and hence allow efficient pumping of the Ho:YAG slab. Previous reports of intracavity pumping have shown that the thulium wavelength can shift to avoid the strong holmium absorption, and in the only other previous report of Tm:YLF intracavity pumping Ho:YAG, [17], the Tm:YLF laser shifted to ~1.95µm, see figure 3. In order to control this effect, and attempt to push operation to the stronger holmium absorption minimum around 1.92µm, we employed high-pass edge mirrors to form the thulium laser cavity.…”
Section: Intracavity Pumping Experimental Designmentioning
confidence: 90%
See 1 more Smart Citation
“…Such a strong absorption, even when partially saturated, should dominate any other losses in the thulium cavity and hence allow efficient pumping of the Ho:YAG slab. Previous reports of intracavity pumping have shown that the thulium wavelength can shift to avoid the strong holmium absorption, and in the only other previous report of Tm:YLF intracavity pumping Ho:YAG, [17], the Tm:YLF laser shifted to ~1.95µm, see figure 3. In order to control this effect, and attempt to push operation to the stronger holmium absorption minimum around 1.92µm, we employed high-pass edge mirrors to form the thulium laser cavity.…”
Section: Intracavity Pumping Experimental Designmentioning
confidence: 90%
“…Although pumping of a holmium laser by placing it inside the cavity of a thulium laser has been demonstrated by several authors, [8,16,17], if the crystals share a common cavity, [8,16], the thermal lensing in both crystals can seriously affect the beam quality of the Ho:YAG output. To tackle this problem, Schellhorn et al, [17], introduced a novel configuration whereby the Ho:YAG laser cavity was partly decoupled from the Tm:YLF cavity by polarization. In our design the two cavities are fully decoupled through the use of side-pumping, which has the further advantage of much less stringent requirements on the beam quality for the thulium pump laser.…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficiency of these systems is usually limited because of the deleterious effect of upconversion losses at high pump level and reverse transfer between the Tm and Ho ions [11] which produce a large thermal load of the crystal and practically prevent an operation at PRF larger than few tens of Hertz. Further work has then focussed on direct in-band pumping of the Ho 5 I 7 manifold by Tm:YLF solid-state laser [12,13] or more recently by suitable laser diodes at 1.9 lm [14] or via a diode-pumped secondary laser source, e.g., a thulium (Tm) fiber laser [15]. Even if the Tm-fiber lasers are diode-pumped in the 790 nm band leading to an a priori large quantum defect, the electrical to optical efficiency (EOE) can be significantly enhanced by the crossrelaxation process where one photon can excite two Tm ions in the 3 H 4 level [11,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ability to tune the output wavelength is another advantage, which let ones to pump other lasers such as Cr:ZnSe [34][35][36][37] or holmium−doped crystalline lasers [38][39][40][41][42][43] etc.…”
Section: Introductionmentioning
confidence: 99%